Urban Cemeteries as Bird Habitat in Cimahi City, West Java Province - Kurnia, Insan (Jurnal Biologi Tropis, 2024)
Cemeteries are a form of green open space (GOS) that are commonly found in various landscapes, both urban and rural.  Its existence becomes a balancer in an environment. However, studies on the ecological role of cemeteries are still very limited, including its role as bird habitat. This study aims to analyze the role of cemetery open space as bird habitat in Cimahi City, West Java Province. The research was carried out in May-June 2021 and May 2022 at 23 cemeteries. Bird data was taken using the cruising method while habitat data described conditions in general. Data were analyzed by qualitatively and quantitaively (chi-square, diversity index, evenness index, and similarity index). The richness of bird species found was 23 species birds. The birds species found varied from only two species (Al Maqom, Cibaligo, Cibaligo Tengah, Kihapit, and Melong RW07) to 13 species of birds (Gunung Bohong). The most widely distributed bird species is the Cave Swiftlet (All locations) followed by the Eurasian Tree Sparrow (18 locations), while six species are only found in one location.  The number of species found differed significantly between cemetery sites (χ²count = 39.90; df=21; P<0.05), as well as the number of individual birds (χ²count = 1659.82; df=21; P<0.05).  The diversity index ranged from 0.50 (Cibaligo) to 2.44 (Gunung Bohong), while the evenness index ranged from 0.66 (Cibodas) to 0.99 (Kihapit).  The similarity index ranged from 0.07-1.00.